Nursing workforce modelling in UK hospices – recommendations for future planning. Issue 2 (1st September 2011) - Roberts, Dai; Hurst, Keith
Abstract : Context: United Kingdom (UK) hospice ward staffing has remained unchallenged for two decades while specialist palliative care provision has changed markedly, bringing new workforce demands. Yet, there has been little evidence to inform hospice workforce structures, which aspire to deliver the highest quality holistic care to specialist palliative care patients and their carers. Workforce planning and development has been described as ensuring that sufficient (but not over-sufficient) and appropriately qualified staff are available, in the right place and at the right time to match service demand. Key elements that influence nurse staffing levels include ward occupancy, patient dependency, nursing activity, workload and staff mix. Method: An evaluation method adapted from a UK-wide nursing workforce planning and development study was used to assess nursing activity in a patient (and carer) dependency context within 13 hospices (16 wards). Findings: A dataset, which profiles and benchmarks hospice ward patient dependency, nursing workload, staff activity, ward establishments, quality and costs in 16 hospice wards has been created. There are marked differences between hospices across the UK within each of the workforce modelling elements. Hospice ward staff face heavier workloads; wards are better staffed and more expensive to run, but deliver higher-quality care than their NHS counterparts. Structural and procedural differences between hospice wards in the study are hard to explain. Conclusions and recommendations: The hospice dataset provides evidence-based recommendations to inform specialist palliative care nursing workforce modelling, including deciding future nursing workforce size and mix based on rising workloads. The new dataset is suitable for use in all UK hospice wards.